Impact of Ross Gyre on surface circulation in the Amundsen Sea, Antarctica - Hailun He (Environmental Research Communications, 2024)
The east limb of the Ross Gyre approaches the western Amundsen Sea, thereby exerting an influence on the surface circulation dynamics. This study investigates the impact of the zonal movement of the eastern boundary of the Ross Gyre on the surrounding surface geostrophic circulation in January. Specifically, a zonal shift of the eastern boundary of the Ross Gyre induces a substantial shelf-basin circulation within the Amundsen Sea. The findings of this study provide valuable insights into the influence of the Ross Gyre on the exchange processes between the Amundsen Sea shelf and basin.